SEHAT DI USIA REMAJA MELALUI PEMBINAAN DAN PEMANTAUAN KESEHATAN SECARA RUTIN - Hendy Suwibowo (Institut Seni Indonesia Surakarta, 2016)
The teens' behavior often invite attention, show egocentricity and attempt to present a desire to appear. The teens have many potencies and it must be managed so that they use it for the right deeds. Based on the reason, then, the writer holds community service entitled